DETERMINANTS OF TRADITIONAL, COMPLEMENTARY, AND ALTERNATIVE MEDICINE (TCAM) CHOICES : A SYSTEMATIC REVIEW - Zainal Abidin; Prastuti Soewondo (Proceedings of the International Conference on Applied Science and Health, 2018)
Background: Traditional, complementary, and alternative medicine (TCAM) is one of the treatment methods that have existed for a long time. The use of TCAM as treatment is increasing in many countries. Extensively, TCAM is used to treat various diseases, especially patients with two or more chronic diseases. TCAM as treatment is chosen by the community based on their HBM (Health Belief Model). This study aims to look at the reasons patients choose to seek treatment at TCAM. Methods: Systematic review with journal tracking through 3 database source, ProQuest, Scopus and Springer Link. We use the keywords “determinants” AND “traditional, complementary, and alternative medicine” for journals published in the last five years. Then we conduct critical appraisal of the selected journals. Results: From the five selected studies , we found that health satisfaction variables are the strongest reason in TCAM choice as treatment. They visit health modalities to improve their well-being or health status. Some believe and agree that TM is more safety, more convenient, more effective, cheaper, and easier to use. The use of TCAM is related to patient satisfaction, TCAM knowledge, outsides influence, positive perception, higher education, and more than 1 chronic illness. All these factors explain the model of peoples belief to health services. Conclusions: Patient satisfaction was strongly predictor of TCAM choices. Their well-being have perceived more better after using TCAM services. The socio-demographic and socioeconomic variables are modifying factors that doesn’t always influence patient decision. All these determinants enrich the HBM theory as follows patient satisfaction, patient knowledge, socio-demographic, socioeconomic, and distrust as barrier.